Supply- and demand-side factors influencing uptake of anemia interventions: Systematic review of evidence from low-and-middle income countries - Gune, Soyra; Avula, Rasmi; Scott, Samuel P.; White, Howard; TV, Bhumika; Gupta, Neha; Yadav, Kapil; Vohra, Kashish (International Food Policy Research Institute, 2025)
This Research Note summarizes findings from a systematic review that included published papers and reports from 27 low-and-middle income countries on barriers and facilitators to uptake of interventions to address anemia. The findings from this review, could inform programs and policies across sectors to strengthen delivery and uptake of interventions for reducing anemia.